3x+120=9x-12

Simple and best practice solution for 3x+120=9x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+120=9x-12 equation:


Simplifying
3x + 120 = 9x + -12

Reorder the terms:
120 + 3x = 9x + -12

Reorder the terms:
120 + 3x = -12 + 9x

Solving
120 + 3x = -12 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
120 + 3x + -9x = -12 + 9x + -9x

Combine like terms: 3x + -9x = -6x
120 + -6x = -12 + 9x + -9x

Combine like terms: 9x + -9x = 0
120 + -6x = -12 + 0
120 + -6x = -12

Add '-120' to each side of the equation.
120 + -120 + -6x = -12 + -120

Combine like terms: 120 + -120 = 0
0 + -6x = -12 + -120
-6x = -12 + -120

Combine like terms: -12 + -120 = -132
-6x = -132

Divide each side by '-6'.
x = 22

Simplifying
x = 22

See similar equations:

| x-1+3x+1+3x=56 | | -32=-6x-8 | | x+1/5=x+5/7 | | 4(2y+1)=(12-y) | | y=x^2-4x-28 | | 260=-u+123 | | -y+233=171 | | 5x+3x=5y-3y | | 15-u=283 | | -6(2x-1)=12x-6 | | x(3-8)=3x-8x | | 2q=1-7 | | (x-5)*6=54 | | 2x-3(2/x) | | 4x^2+3x=18 | | z^3-(4-3i)z^2+(9-2i)z-2+11i=0 | | 2[3lnx-ln(x+1)-ln(x-1)]= | | 3x=(20/7)-x | | (4+7i)(5-3i)= | | 20-5x=32+7x | | 7(7x-5)= | | 15=3xy | | 5x^2+3y^2=0 | | 10x^2+3y^2=2 | | 12n+4n=16n^2 | | 12n+4n=16n | | 12n+4n=16 | | 3x+50=2x+10 | | =3lnx | | x+26=2x+18 | | 7x+11=6x+3 | | 2x^2+18=x^2+9x |

Equations solver categories